2015
DOI: 10.1073/pnas.1501555112
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic reprogramming in triple-negative breast cancer through Myc suppression of TXNIP

Abstract: Triple-negative breast cancers (TNBCs) are aggressive and lack targeted therapies. Understanding how nutrients are used in TNBCs may provide new targets for therapeutic intervention. We demonstrate that the transcription factor c-Myc drives glucose metabolism in TNBC cells but does so by a previously unappreciated mechanism that involves direct repression of thioredoxin-interacting protein (TXNIP). TXNIP is a potent negative regulator of glucose uptake, aerobic glycolysis, and glycolytic gene expression; thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
202
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(213 citation statements)
references
References 44 publications
10
202
1
Order By: Relevance
“…6D). These findings suggest that c-Myc functions as a promoter of TXNIP transcription, which is consistent with observations from the study of triple-negative breast cancer (27).…”
Section: Txnip Is a Negative Regulator Of Glucose Metabolismsupporting
confidence: 91%
See 2 more Smart Citations
“…6D). These findings suggest that c-Myc functions as a promoter of TXNIP transcription, which is consistent with observations from the study of triple-negative breast cancer (27).…”
Section: Txnip Is a Negative Regulator Of Glucose Metabolismsupporting
confidence: 91%
“…Among the altered glycolysisrelated genes in the database, we selected TXNIP as the target gene and investigated whether FBW7 regulates glycolysis via TXNIP in PDAC. TXNIP has been identified as a tumor suppressor gene in various solid tumors and hematologic malignancies (27). Moreover, recent evidence indicates that TXNIP also functions as a potent negative regulator of glucose uptake and aerobic glycolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, MLX has recently been shown to coordinately regulate a subset of target genes with c-Myc (Shen et al 2015) and to be necessary for survival of Myc-driven tumors . We found that c-Myc occupancy at the Txnip promoter is reciprocal to MLX and likely mediated by E-boxes contained within the CHORE motifs (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In TNBC, metabolic dysregulation is driven by factors such as glutathione S-transferase Pi 1 (GSTP1), forkhead box O 3a (FOXO3a), and EGFR-induced c-Myc (4345). Specifically, c-Myc represses thioredoxin-interacting protein (TXNIP), an inhibitor of glycolytic gene expression and glucose uptake (46). Recent work has identified TXNIP as a suppressor of breast cancer metastasis, which strengthens the mechanistic link between metabolism and metastasis (47).…”
Section: Breast-to-brain Metastasesmentioning
confidence: 99%